REPRODUCTIVE DISORDERS IN DECCANI EWES: AN ABATTOIR STUDY - SUDHAKAR, T; RAO, K SADASIVA; RAJU, K G SOLMON; ANJANEYULU, Y (The Indian Journal of Animal Reproduction, 2023)
An abattoir survey of 3004 genital tracts of Deccani breed ewes revealed gravid ( 1.06 per cent) and abnormal genital tracts (6.52 per cent). The incidences of anatomical and pathological abnormalities were 2.94 and 3.4 per cent, respectively. Among the percentage of anatomical abnormalities, Parovarian cyst 1.89), kinked cervix (0.99) and hypoplasia of ovaries (0.06) 1;yere noticed. The incidence of pathological abnormalities (per cent) were ovarian cysts (0.12), ovaro burs al adhesions (0.49), ovulation tags 0.13, endometritis (0.76), pyometra (0.49), melanin pigmentation (0.66), hydrometra (0.03), mummification (0.06) and maceration (0.03).